Conflict of virtual and reality in interior design studio: Assessment of student success rates - Güley, Kamil; Akalın, Nisan (My University, 2025)
This study evaluates the relative efficiency of interior architecture education programs delivered through face-to-face education (FFE) compared to online education (OE), from the perspectives of both students and educators. The quality of learning, as perceived by educators, was assessed through the analysis of semester grades assigned after each academic term. Conversely, the student perspective was gathered via a structured questionnaire. This research addresses a notable gap in existing literature regarding student success by incorporating the educators' viewpoints into the analysis with a comparative analysis examining student success rates between FFE and OE. This investigation, from the student perspective, found the FFE model to be a more effective educational approach compared to the OE model. The disparity between the instructors' perspectives was not significant. Nevertheless, valuable insights were obtained from educators utilizing the OE model, especially regarding their experiences during the pandemic. These insights could inform future research on hybrid educational models. As a result, this study advocates for the implementation of a hybrid educational model as a progressive direction for interior architecture education.
Keywords: Online education; Pandemics; student success; face-to-face education; design studio courses